Programming language semantics: It’s easy as 1,2,3 - HUTTON, GRAHAM (Journal of functional programming, 2023)
Programming language semantics is an important topic in theoretical computer science, but one that beginners often find challenging. This article provides a tutorial introduction to the subject, in which the language of integers and addition is used as a minimal setting in which to present a range of semantic concepts in simple manner. In this setting, it is easy as 1,2,3.